Experimental research on the effect of graphite on heat transfer performance of a latent heat storage system - Zhao, Yuanyuan; Li, Guang; Zhang, Xinzhi; Wu, Hongqiang (Frontiers in Energy Research, 2023)
Phase change materials (PCMs) provide a good resolution for the latent heat storage system which can be used in many application fields such as solar energy utilization and waste heat recovery. This study aims to experimentally investigate the impact of graphite powder on the thermal characteristics and heat transfer performance of paraffin with ceresin (PC) as a PCM, using water as the heat transfer fluid. Experimental tests were conducted to analyze the heat transfer performance of PC and the influence of graphite powder on its thermal characteristics. Different masses of graphite powder were employed to assess their effects on the heating rate and the time required for PC to reach its melting temperature. The experimental results revealed that the addition of graphite powder improved the heating rate of both PC and water, attributed to its high thermal conductivity. Furthermore, the time for PC to reach the melting temperature was decreased with varying amounts of graphite powder, achieving a maximum reduction of 17.2% with the addition of 40 g of graphite powder. However, the effectiveness of graphite powder in enhancing heat transfer efficiency was found to be limited, with the optimal promotion effect observed at around 40 g of graphite powder for 500 g of PC. The findings of this investigation provide valuable insights for the design of phase change energy storage systems, with potential applications including heat pump drying units, greenhouse energy storage in modern agriculture, and solar energy storage utilization technology. The theoretical basis established can contribute to the development and optimization of PCM-based systems in diverse practical scenarios.